2016
DOI: 10.1007/s00702-016-1605-7
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive action of botulinum toxin type A in carrageenan-induced mirror pain

Abstract: Abstract"Mirror pain" or mirror-image pain (MP) is pain opposite to the side of injury. Mechanism and frequency in humans is not known. There is no consent on therapy. Here we report that unilaterally injected botulinum toxin type A (BT-A) has bilateral effect in experimental MP, thus deserves to be investigated as therapy for this condition. We examined the localization of BT-A's bilateral antinociceptive action in MP induced by 3% carrageenan intramuscular injection in Wistar rats. BT-A was applied periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…For now there is no experimental evidence for that. In experiments by Antonucci et al (2008) (Bach-Rojecky et al, 2005, 2010a, 2010b, Bach Rojecky and Lacković 2009Matak and Lacković 2014;Drinovac et al, 2016) and the group of Pavone and Luvisetto (Luvisetto et al, 2006(Luvisetto et al, , 2007(Luvisetto et al, , 2015Marinelli et al, 2012;Pavone and Luvisetto 2010;Mika et al, 2011) Mazzocchio and Caleo 2015). Similar findings were obtained in quadriceps muscle of stroke-related spastic patients after BoNT/A injection into soleus muscle .…”
Section: Detection Of Truncated Snap-25 Fragments In Cns After Periphsupporting
confidence: 59%
“…For now there is no experimental evidence for that. In experiments by Antonucci et al (2008) (Bach-Rojecky et al, 2005, 2010a, 2010b, Bach Rojecky and Lacković 2009Matak and Lacković 2014;Drinovac et al, 2016) and the group of Pavone and Luvisetto (Luvisetto et al, 2006(Luvisetto et al, , 2007(Luvisetto et al, , 2015Marinelli et al, 2012;Pavone and Luvisetto 2010;Mika et al, 2011) Mazzocchio and Caleo 2015). Similar findings were obtained in quadriceps muscle of stroke-related spastic patients after BoNT/A injection into soleus muscle .…”
Section: Detection Of Truncated Snap-25 Fragments In Cns After Periphsupporting
confidence: 59%
“…acidic saline induced “mirror pain,” BoNT/A injected into the ipsilateral hind paw pad significantly reduces mechanical hypersensitivity on the injured but also on the uninjured contralateral side [104]. Bilateral effect of BoNT/A was repeatedly shown in other bilateral pain models, like in trigeminal neuropathy induced by unilateral infraorbital nerve constriction injury (IoNC) [86], inflammatory pain induced by complete Freund’s adjuvant (CFA) injection into temporomandibular joint [22], and hyperalgesia after carrageenan injection into the calf muscle [24]. The toxin’s bilateral effect after unilateral injection was demonstrated in poly-neuropathic states evoked by systemic paclitaxel [82] or streptozotocin [83], as well as in the model of bilateral acute model of s.c. carrageenan-induced inflammatory hyperalgesia [94].…”
Section: Actions Of Bont/a In the Central Nervous Systemmentioning
confidence: 99%
“…The role of the endogenous opioid system in neuromodulation and control of pain is well known. It was suggested that spinal opioid system is involved in antinociceptive effects of BT‐A (Drinovac et al., ; Drinovac Vlah et al., ). This assumption was based on the result that intrathecal opioid antagonists, naltrexone or naloxonazine, dose‐dependently inhibit the antinociceptive effect of peripherally applied BT‐A (Drinovac et al., ; Drinovac Vlah et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that spinal opioid system is involved in antinociceptive effects of BT‐A (Drinovac et al., ; Drinovac Vlah et al., ). This assumption was based on the result that intrathecal opioid antagonists, naltrexone or naloxonazine, dose‐dependently inhibit the antinociceptive effect of peripherally applied BT‐A (Drinovac et al., ; Drinovac Vlah et al., ). In parallel, those antagonists prevent BT‐A‐mediated reduction in c‐Fos expression, a marker of neuronal activation, in dorsal horn (Drinovac et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation